The Effect of Giving Petrovita to Caisim Mustard Plants (Brassica Juncea L.) (At the Pilot Garden of the Bitung City Agriculture and Food Security Service, North Sulawesi) - Stella T. Kaunang; Saroinsong, Deedy E. I. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Caisim plant or Brassica juncea var. Tatsai is a type of vegetable that is popularly consumed by Indonesian people. Caisim has high nutritional value and can grow well in various types of soil. sustainable livestock business. Method of Implementing Internships, Setting Internship Goals and conducting observations or interviews. The caisim mustard plant or Brassica juncea L. is a member of the Brassicaceae family which is also home to radishes, broccoli and cabbage. It is distinguished by having four cross-shaped flower petals. Mustard plants contain many vitamins and minerals. Vitamin levels in the form of K, A, C, E, folate, and contain alkaloids, flavonoids, saponins, amino acid tryptophan and dietary fiber.